CompTIA PenTest+ study guide exam PT0-003 - Chapple, Mike 1975-; Shimonski, Robert; Seidl, David (John Wiley and Sons, Inc., 2025)
Prepare for the CompTIA PenTest+ certification exam and improve your information security job performance with Sybex In the newly revised third edition of the CompTIA PenTest+ Study Guide: Exam PT0-003, renowned information security professionals Mike Chapple, Rob Shimonski, and David Seidl deliver a comprehensive and up-to-date roadmap to succeeding on the challenging PenTest+ certification exam. Freshly updated to track the latest changes made to Exam PT0-003, the book will prepare you not just for the test, but for your first day at your first or next information security job. From penetration testing to vulnerability management and assessment, the authors cover every competency tested by the qualification exam. You'll also find: Complimentary access to the Sybex online learning environment, complete with hundreds of electronic flashcards and a searchable glossary of important terms Up-to-date info organized to track the newly updated PT0-003 PenTest+ certification exam Quick reference material and practice tests designed to help you prepare smarter and faster for the test Succeed on the PT0-003 exam the first time. Grab a copy of CompTIA PenTest+ Study Guide and walk into the test--or your new information security job--with confidence.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed March 10, 2025)
Keywords: Computer networks -- Study guides -- Security measures -- Examinations; Penetration testing (Computer security) -- Study guides -- Examinations; Telecommunications engineers -- Study guides -- Certification -- Examinations; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Tests d'intrusion; Examens; Guides de l'étudiant